The effect of selected WEDM parameters on cut surface quality of 2017A aluminum - Gałda, Lidia; Jamróz, Konrad (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2024)
With the wire electrical discharge machining (WEDM), good quality machined surfaces can be achieved. The WEDM is worth considering for machining fasteners used in assembly processes. This paper presents a study of the WEDM cutting process of aluminum 2017A using an WEDM machine of the FR 400 type. After applying different cutting speeds, the characteristics of the cut surface were evaluated. Despite some differences in the shape of surface profiles and surface morphology noted after WEDM cutting at different speeds, the analysis of variance concluded that the WEDM cutting speed in the studied variation range of 23-125 μm/s has no significant effect on surface roughness. At the highest speed studied, machining efficiency can be increased, affecting cost and energy reduction, while maintaining an acceptable and comparable level of surface quality after WEDM cutting.